APPLICATION OF COOPERATIF LEARNING MODEL TYPE THINK PAIR SHARE (TPS)TO IMPROVE STUDENT LEARNING APPLY OUTCOMES IPS CLASS IV SD NEGERI 013 PADANG SAWAH KECAMATAN KAMPAR KIRI - Noviana, Eddy Noviana; ', Irman; ', Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :This study aims to improve the learning outcomes of students in grade IV IPS Elementary School 013 Padang Sawah 2013/2014 school year. The subjects were students of SD Negeri IV class Padang sawah 013 by the number of students by 28 students. The study was a collaborative classroom action research with three cycles. Research data shows that the learning outcomes of students has increased. The research was conducted on Februari 25 2014 to Maret 29, 2014 by 3 cycles. Subjects were students of SDN 013 Padang Sawah, totaling 28 people who use the data source. The data collection instruments in this thesis is a teacher and students activities sheets and students achievement. This thesis presents the results obtained each day before the actionÂ  an improve in base score cycle with the average being 56,42. In the first cycle improve an average of 61,60 with increase big as 9,18% and an improve in the second with an average of 71,78 with increase big as 27,22%. Activities of the teacher in the learning process in cycle of 54,16 with increase big as 46,15% and the second meeting improve Â to 62,5% and the second meeting improve 62,5%. Cycle II first meeting and the second meeting improve 75% to 79,16% and the second meeting impove 79,16%. In the third cycle of the first meeting and the second meeting improve 87,5% to 91,66% and the second meeting impove 95,83%. Results of data analysis of students activities in the first cycle with the first meeting of an average of 50% and a second meeting improve to 62,5% and a second meeting improve to 79,16%. At the first meeting of the second cycle with an average of 91,66% Results in the class IV at SDN 013 Padang Sawah that the implementation of cooperative learning model of Think Pair Share (TPS) can improve the student achievement of social studiesat fourth graderes SDN 013 Padang Sawah. Key Words: Cooperatif Learning Think Pair Share (TPS), Learning Outcomes IPS